Respuesta :

12-13= yx this is that expression


Simplifying
12x + -1(6 + 7x) = 0
12x + (6 * -1 + 7x * -1) = 0
12x + (-6 + -7x) = 0

Reorder the terms:
-6 + 12x + -7x = 0

Combine like terms: 12x + -7x = 5x
-6 + 5x = 0

Solving
-6 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 5x = 0 + 6
5x = 0 + 6

Combine like terms: 0 + 6 = 6
5x = 6

Divide each side by '5'.
x = 1.2

Simplify
ACCESS MORE